Earthquake Preparedness in Teaching Hospitals: a cross-sectional study in Yazd/ Iran - Mahdieh Abedi; Khatere Khanjankhani; Mohammad mehdi Kiani; Seyed Abdel Hossein Mousavi Rigi; Marzieh Salehi (Kerman University of Medical Sciences, 2017)
Introduction: Since it is not possible to accurately predict the time of earthquake, knowledge and preparedness of hospitals in relation to earthquake and strategies of facing earthquake are of a particular importance. The aim of this study was to evaluate the rate of earthquake preparedness in hospitals affiliated to Yazd University of Medical Sciences. Methods: This was a cross-sectional descriptive-analytic study performed in four hospitals affiliated to Yazd University of Medical Sciences in 2015. A checklist including123 questions evaluating the safety of hospitals in facing earthquake in eight dimensions were used Data analysis was performed using descriptive statistics and Pearson correlation and through SPSS16 statistical software package. Results: The hospitals' preparedness against earthquake disaster was 58.87%. The highest rate of preparedness was found for dimension of disaster management plans and the lowest rate of preparedness was related to the dimension of hospital training plans (89.08% vs. 25%). The highest correlation was between the number of hospital beds and the dimension of safety of hospital equipments (r=.987) and the lowest correlation was between the number of hospital beds and the training plans (r=.271). Conclusion: Generally, hospitals preparedness against earthquake was at a moderate level and since the lowest level of preparedness against earthquake was in the dimension of educational planning, implementation of training courses should be considered as a priority. Keywords: Readiness, Teaching hospital, Earthquake. Citation: Abedi M, khanjankhani K, Kian MM, Mousavi Rigi SA, Salehi M. Earthquake Preparedness in Teaching Hospitals: a cross-sectional study in Yazd/ Iran. Journal of Health Based Research 2017; 3(1): 1-11.